Study of the slant fracture in solid and hollow cylinders: Experimental analysis and numerical prediction (Fracture and Structural Integrity, 2022)
This paper is devoted to the numerical and experimental study of ductile fracture in bulk metal forming of the 2017A-T4 aluminum alloy. From an experimental standpoint, the ductile fracture of the 2017A-T4 aluminum alloy is investigated under compressive load. Two cross-sections of solid and hollow specimens are considered. The mechanical behavior and the microstructure of the 2017A-T4 aluminum alloy were characterized. It is found that the well-known barrel shape is obtained when a compressive load is applied. Analyses of fracture topographies show a ductile fracture with dimples under tension and coexistence of ductile fracture with dimples and slant under compression. The classical physically-based Gurson-Tvergaard-Needleman (GTN) model and its extension to incorporate shear mechanisms to predict failure at low-stress triaxiality are considered. These two models have been extended to take into account the thermal heating effect induced by the mechanical dissipation within the material during the metal forming process. The two models have been implemented into the finite element code Abaqus/Explicit using a Vectorized User MATerial (VUMAT) subroutine. Numerical simulations of the forging process made for hollow and solid cylindrical specimens show good agreement with experimental results. In contrast with the GTN model, the modified GTN model incorporating shear mechanisms can capture the final material failure.
Keywords: Physically-based model; Ductile fracture; Thermomechanical coupling; Slant fracture; Shear mechanisms; Numerical implementation